Assessing farmer perceptions about the available financing mechanisms and financial services – the case of the seed potato industry in South Africa - Manuel, Jaime (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.